Evaluation of Aeromodelling Sports Achievement Development at the 2019 National Sports Games Training center of Central Java Province (Journal of Physical Education and Sports, 2022)
The development of Aeromodelling Achievements in Central Java through the All-Indonesian Aeromodelling Federation (FASI) in Central Java is not optimal, as evidenced by the achievements in 2016 PON and 2018 National Championships which are still inferior to other provinces. Based on this, it is necessary to evaluate the development of Aeromodelling achievements in Central Java. The purpose of this study was to evaluate the development of Aeromodelling Achievement in the province of Central Java, especially during the 2019 PON Training center period. The evaluations carried out included Context (Background and Objectives), Input (Recruitment of Trainers and Athletes, Facilities and Infrastructure), Process (Exercise Program, Transportation, Coordination, Funding, Consumption) and Product (Achievements). The instruments used in this research are observation, interview and documentation. The result of this research is that the context aspect has a good vision, mission and goals. The input aspect shows the recruitment of coaches and athletes in accordance with the provisions, the condition of facilities and infrastructure needs to be improved again. Process aspect shows the training program is clear, transportation is very lacking. coordination, funding, and consumption need to be improved. Product aspect shows a pretty good performance. The conclusion of the research from the four evaluation factors at the Central Java Aeromodelling Training center is good enough, but some improvements and improvements need to be made in order to compete for optimal performance.